(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In the expediente we present the UrdimentoEditorial Team, that is, the body of editors, associate editors, thematic dossier, editorial board and the body the reviewers in the issue of Urdimento. We also introduce the editorial support team.